ISLAND AND ANABRANCHING GENERATION PROCESSES – A COMPARATIVE REVIEW IN THE UPPER PARANÁ RIVER - Leli, Isabel Terezinha; Hayakawa, Ericson Hideki; Santos, Vanessa Cristina dos; Stevaux, José Cândido (Revista Brasileira de Geomorfologia, 2021)
Although the anabranching channel pattern is frequent in rivers of different sizes and climates, understanding the processes involved in its genesis requires further research, especially focusing on island formation. This article discusses the processes involved in anabranching patterns and island formation, focusing on the environmental characteristics and sedimentary records in a stretch of the Upper Paraná River - PR. We compare the results with concepts and definitions in the literature. Islands in the Upper Paraná River form in two ways: from 1) the stabilization of central bars (in-channel processes) and 2) the floodplain cutoff (off-channel processes). The islands of the first case are generally smaller and younger than those formed by off-channel processes. Both islands can expand their surface by attaching lateral bars. Multi-channeling, island formation, and permanence can be explained through the concept of maximum flow efficiency.